Peningkatan Kesadaran Akan Pentingnya Kelembaban Kulit Melalui Skrining Hidrasi Kulit Pada Masyarakat Kelurahan Tanjung Duren Selatan - Moniaga, Catharina Sagita; Santoso, Alexander Halim; Gunaidi, Farell Christian; Zhalila, Zhillan; Marcella, Agnes (jurnal ABDIMAS Indonesia, 2025)
Adequate skin hydration is essential for maintaining skin elasticity, softness, and overall barrier function. Insufficient hydration can lead to various skin health issues, one of the most common being dry skin. This condition is more prone to irritation, itching, and cracking, which can increase the risk of infection. The Community Service Program (PKM) conducted in Tanjung Duren Selatan aimed to raise public awareness about the importance of maintaining skin moisture through educational activities and hydration level screening using a skin analyzer. This program was carried out using the Plan-Do-Check-Act (PDCA) approach, including skin hydration assessments and education on risk factors, the impact of skin dehydration, and appropriate skincare strategies. Of the 104 participants, 68 individuals (65.38%) were found to have low skin oil levels, and 82 individuals (78.85%) had low skin water content, indicating dry skin conditions. These results highlight the importance of skin hydration screening as an early detection tool for skin health risks and as a foundational step to promote preventive skincare awareness in support of overall health and quality of life.